Impact of Tourist Experience on Satisfaction and Revisit Intention: A Bibliometric Review and Content Analysis - Irene Kanina Ratih; Lissa Rosdiana Noer (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The tourism industry is currently experiencing significant growth and plays a pivotal role in the global economy and contributes significantly to the global Gross Domestic Product (GDP). However, research examining the tourism industry will decline in 2024, especially those related to the topic of the influence of tourist experiences on satisfaction and intention to visit again. So, it is important to conduct further research to enrich research in similar fields and topics. This study aims to map the trend, conceptual structure, and know what kind of tourist experience are used to influence satisfaction and revisit intention in tourism research using bibliometrics and content analysis method, with data sourced from the Scopus and Web of Science databases, totaling 155 papers. From these papers, it is evident that the trends or keywords strongly related to this study's topic are